2021
DOI: 10.1016/j.nicl.2021.102631
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive control network connectivity differentially disrupted in treatment resistant schizophrenia

Abstract: Highlights Mechanisms underlying treatment-resistant schizophrenia are unclear. Effective connectivity within cortico-striatal network differentially disrupted in resistant patients. Resistance associated with lack of top-down control and aberrant glutamate function. We suggest a subtype of schizophrenia with distinct neurobiological mechanism. Results are important for guiding treatment strategies and developing new d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…For example, a reported significant alteration in cognitive flexibility in TRS is believed to tap into a distinct underlying neurobiological mechanism and may inform future treatment strategies (e.g. glutamatergic targets and giving clozapine earlier in resistant patients) (Horne et al, 2021). Our findings suggest that language-related tasks, and potentially verbal memory and learning tasks, have likely applications in multidisciplinary strategies to elucidating the pathophysiology of TRS and to developing predictive models and personalised medical approaches.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a reported significant alteration in cognitive flexibility in TRS is believed to tap into a distinct underlying neurobiological mechanism and may inform future treatment strategies (e.g. glutamatergic targets and giving clozapine earlier in resistant patients) (Horne et al, 2021). Our findings suggest that language-related tasks, and potentially verbal memory and learning tasks, have likely applications in multidisciplinary strategies to elucidating the pathophysiology of TRS and to developing predictive models and personalised medical approaches.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that while the RPE signal generation was intact in treatment-resistant patients, the cognitive control needed to overcome the emotional bias to make optimal predictions was impaired. We were then able to use dynamic causal modelling to demonstrate that while the treatment-responsive patients had increased top-down connectivity from ACC to sensory regions (fusiform gyrus and amygdala) and reduced connectivity from all regions into the striatum during this task, the treatment-resistant group did not show any enhanced top-down connectivity from the ACC ( Horne et al, 2021 ). This supported the proposition that increased cognitive control - indexed by enhanced top-down connectivity over incoming sensory information - may provide the striatum with contextual information to appropriately integrate with incoming sensory information in treatment responsive patients.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the absence of this top-down cognitive control may contribute to persistence of psychotic symptoms in the treatment-resistant patients. Moreover, top-down connectivity from ACC to sensory regions was inversely related to positive symptoms in the treatment-responsive group further suggesting that effective cognitive control may be important in controlling positive symptoms ( Horne et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that our findings were observed in the real-world context of TRS that included failed antipsychotic trials and concomitant use of non-CLZ, D2 receptor-blocking antipsychotic drugs. TRS may represent a pathophysiologic subtype of schizophrenia characterized by more global disruptions in functional connectivity and a unique pattern of activation of cognitive systems (Ganella et al 2017 ; Horne et al 2021 ). Furthermore, evidence from positron emission tomography studies implicate a non-DA signature of illness, relative to responders of non-CLZ antipsychotic drugs (Demjaha et al 2012 ; Kim et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%